Słownictwo rzadkie w polszczyźnie Jana Kochanowskiego - Kucała, Marian (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
If we compare The Dictionary of Jan Kochanowski with the Dictionary of Polish Language of the 16th Century it becomes obvious that Jan Kochanowski rarely used religious vocabulary (with the exception of the word God), as well as numerals, words with particles, e.g. chociaż (“although”) appearing in the Dictionary of Polish Language of the 16th Century as many as 1061 times. Similar situation applies to other words. Kochanowski rarely used neologisms and introduced hapax legomena into his texts mainly for the reasons of poetics.